Índice para classificação da qualidade da água para irrigação - Rodrigues, Kelly Kaliane Rego da Paz (2010)
Given the scarcity of good quality water in the Brazilian semi-arid northeast is necessary to resort to the use of lower quality water, so there must be planning to allow the best use of these waters. One way of classifying water quality is by means of indexes, which can summarize a series of parameters in a single number, facilitating the interpretation of long lists of variables or indicators, allowing the classification of water quality. Thus, the object of this study was to develop an index based on statistics to classify the water according to the Irrigation Water Quality Index (IQAI), to evaluate the ionic composition of irrigation water, and sort it by source. To accomplish these tasks, a database was used, which was generated during the Technology Generation and Adaptation Program (GAT), starting in 1988, when water samples were collected monthly from sources in the states of Paraiba, Rio Grande do Norte and Ceara, where the sampling period was of 34, 19 and 11 months, respectively. To evaluate water quality, the electrical conductivity of irrigation water (EC) was taken as reference, which value corresponds to 0,7 dS m-1. Physical-chemical parameters used in this study were: pH, EC, Ca, Mg, Na, K, Cl, HCO3, CO3 and SO4. These values were to calculate RAS (Sodium Absorption Ratio) and EqCaCO3 (Calcium Carbonate Equivalent); plus the following relations: Na/Cl, Ca/Mg, Na/Ca and HCO3/Cl. Data of all variables showed adjustment to normality, tested by Lilliefors method. Afterwards, the irrigation water quality index was determined by means of one equation relating the standardized value a variable correlated with the number of characteristics evaluated. Thus, IQAI was classified from indices, considering the normal distribution. Finally, these indices were subjected to regression analysis, thus allowing evaluating the sensitivity of the indices as a function of EC, by means of the slope adjusted for each source. The proposed methodology for IQAI allowed classifying satisfactorily the irrigation water quality, and to make its estimative based on the EC of the three sources. Ionic composition variation was observed among the three sources and in a same source. Although different water qualities were classified, there was predominance of good quality water, with a quality index of II.